Performance simulation to understand the effects of multi-fluid scaling of gas turbine components for Generation IV nuclear power plants - Osigwe, Emmanuel O.; Gad-Briggs, Arnold; Nikolaidis, Theoklis; Pilidis, Pericles; Sampath, Suresh (ASME, 2019)
A significant hurdle in the development of performance simulation tools to analyse and evaluate nuclear power plants (NPP) is finding data relating to component performance maps. As a result, Engineers often rely on an estimation approach using various scaling techniques. The purpose of this study is to determine the component characteristics of a closed-cycle gas turbine NPP using existing component maps with corresponding design data. The design data is applied for different working fluids using a multi-fluid scaling approach to adapt data from one component map into another. The multi-fluid scaling technique described herein was developed as an in-house computer simulation tool. This approach makes it easy to theoretically scale existing maps using similar or different working fluids without carrying out a full experimental test or repeating the whole design and development process. The results of selected case studies show a reasonable agreement with available data. The analyses intend to aid the development of cycles for Generation IV NPPs specifically Gas-cooled Fast Reactors (GFRs) and Very High-Temperature Reactors (VHTRs).
Keywords: Fluids; Simulation; Nuclear power stations; Gas turbines; Design; Engineers; Computer simulation; High temperature; Very high temperature reactors; Fast neutron reactors